ANALYSIS OF THE CIDOC-CRM CONCEPTUAL MODEL FROM THE BASIC PRINCIPLES OF DESCRIPTIVE CATALOGING IN MUSEUMS - Reis, Mateus da Silva [UNESP]; Castro, Fabiano Ferreira de; Fujita, Mariangela Spotti Lo pes [UNESP] (Univ Murcia, 2023)
Conceptual models are intended to describe and organize concepts from a given domain in order to establish semantic bridges between various information resources in different contexts. In this perspective, the Conceptual Reference Model (CRM), formulated by the International Committee for Documentation (CIDOC), presents itself as a conceptual reference model for museum institutions and collections, aiming to integrate, represent, and relate museum objects to various cultural sources by means of entities and properties. Even though it is focused on the museum reality, this study starts from the problem of investigating whether the CIDOC-CRM conceptual model is in line with the statements and principles that define concepts, research tools, and steps of descriptive cataloging in museums. With this, we aimed to analyze the CIDOC-CRM conceptual model from the formulation of basic principles of descriptive cataloging in museums, seeking to discuss its effective use in the context of semantic relationships among museum collections. This is a descriptive and bibliographic study, and its methodological approach is based on bibliographic review and direct observation. As a result, it was noted that the model performs its semantic relations based on values related to the sphere of meaning and symbolism, pluralizing the existence of the museum object in different environments, and focusing on the improvement of international museum information networks. In conclusion, the results obtained made it possible to evidence that CIDOC-CRM is an excellent alternative for the registration of data and for their association in the informational panorama of collections.
Keywords: Conceptual models; CIDOC Conceptual Reference Model; descriptive cataloging; documentation in museums